Amorfino as a Lyrical Genre of Oral Tradition - Pérez Martínez, Javier (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper studies “copla de amor montubia” [Montubia love couplet] –better known in the Ecuadorian coast as “amorfino”. The research, regarding this type of oral lyric poetry, emphasizes in its formal and thematic characteristics. Therefore, it is shown some differences and similarities between popular poetry and lyric poetry. From the theorization of these two ways of poetry, it is showed the similarity of popular poetry and Hispanic folklore. Additionally, it is highlighted the anthropological point of view due to its social contexts. This form of poetry is stablished in the “montubio” mourning, which is a traditional and ludic way of life of the Ecuadorian peasants from the coasts. In this tradition, there are “juegos de rueda” [traditional rounds] which have worked as a form of erotism, social life, and as way to stablished social attachment.